Pengaruh Book Tax Differences, Arus Kas Operasi, dan Ukuran Perusahaan terhadap Persistensi Laba (Studi Empiris pada Perusahaan Pertambangan yang terdaftar di BEI Periode 2015-2019) - Mira Permatasari (Pascasarjana Universitas Sultan Ageng Tirtayas, 2023)
This study aims to examine the effect of book tax differences, operating cash flow, and company size on earnings persistence in mining companies listed on the Indonesia Stock Exchange for five years (2015-2019). The population in this study were mining companies listed on the Indonesia Stock Exchange. The sample technique used was purposive sampling method. The data analysis technique used is regression analysis. The results of this study show the book tax differences impact on earnings persistence, while operating cash flow and firm size have no effect on earnings persistence.